Work-Related Migration and Poverty Reduction in Nepal - Lokshin, Michael; Bontch-Osmolovski, Mikhail; Glinskaya, Elena (World Bank, Washington, DC, 2012)
Using two rounds of nationally representative household survey data in this study, the authors measure the impact on poverty in Nepal of local and international migration for work. They apply an instrumental variable approach to deal with nonrandom selection of migrants and simulate various scenarios for the different levels of work-related migration, comparing observed and counterfactual household expenditure distribution. The results indicate that one-fifth of the poverty reduction in Nepal occurring between 1995 and 2004 can be attributed to increased levels of work-related migration and remittances sent home. The authors also show that while the increase in work migration abroad was the leading cause of this poverty reduction, internal migration also played an important role. The findings show that strategies for economic growth and poverty reduction in Nepal should consider aspects of the dynamics of domestic and international migration.